Review of the leafhopper genus Anufrievia Dworakowska (Hemiptera: Cicadellidae: Typhlocybinae: Erythroneurini) - Cao, Yanghui; Yang, Meixia; Lin, Shuanghu; Zhang, Yalin (Zootaxa, 2018)
General characteristics of Anufrievia Dworakowska and a key to the species from China and Thailand are provided. Twenty-one new species, Anufrievia adaucta, A. arcuata, A. curva, A. expensa, A. falcata, A. forcipiformis, A. fusina, A. jinghongensis, A. liubanus, A. parisakazu, A. plana, A. qinlingensis, A. quadrata, A. sphenoides, A. subapicifixa, A. subdentata, A. sufflata, A. symmetrica, A. triangulata, A. triprocessa and A. wolongensis are described. Four species are newly recorded from China: A. akazu (Matsumura), A. badjawae Dworakowska, A. bauhinicola Dworakowska & Viraktamath and A. zelta Dworakowska. A. badjawae is also a new record to Thailand.